Reactions towards organizational change: a systematic literature review - Khaw, Khai Wah; Alnoor, Alhamzah; AL-Abrrow, Hadi; Tiberius, Victor; Ganesan, Yuvaraj; Atshan, Nadia A. (Current psychology (New Brunswick, N.J.), 2023)
Regardless of the prevalence and value of change initiatives in contemporary organizations, these often face resistance by employees. This resistance is the outcome of change recipients’ cognitive and behavioral reactions towards change. To better understand the causes and effects of reactions to change, a holistic view of prior research is needed. Accordingly, we provide a systematic literature review on this topic. We categorize extant research into four major and several subcategories: micro and macro reactions. We analyze the essential characteristics of the emerging field of change reactions along research issues and challenges, benefits of (even negative) reactions, managerial implications, and propose future research opportunities.